APPLYING TWO STAY - TWO STRAY STRATEGY TO IMPROVE STUDENTS' READING COMPREHENSION - Sukmayati (English Education Department, 2014)
This study aims to improve students’ reading comprehension of review text using Two Stay-Two Stray strategy. The subject of this study was 23 students of the twelfth year of SMA Laboratorium Unsyiah; thai is XII-IPS. This study was a collaborative action research design which consists of four main steps: planning, acting, observing, and reflecting. It was conducted in two cycles and each cycle consists of two meetings. The data was taken from quiz, observation checklist and field notes. The findings indicate that using Two Stay-Two Stray strategy can improve the students’ comprehension of review text as well as the students' participation. The number of students that reach the minimum standard score in cycle 1 is 64% while in cycle 2 increases to be 87%. The average of students’ involvement in Cycle 1 was 71% (16 students were actively involved) and the average of students’ involvement in Cycle 2 was 86% (19 students were actively involved). It means that the success indicator was reached in cycle 2. Based on the findings, it can be concluded that Two Stay Two Stray strategy is effective in improving students' reading comprehension and active participation. Therefore, it is recommended that this strategy can be used as an alternative strategy in teaching reading.